2014
DOI: 10.1080/0972060x.2014.884778
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of AlgerianInula viscosaleaves

Abstract: The steam distillated essential oil issued from leaves of Algerian Inula viscosa (L.) Aiton were investigated by GC-MS analyses. 23 constituents were identified accounted for 80 % where isocostic acid (56.83 %), fokienol (14.6 %) were the major constituents. This plant becomes richer in fokienol and its flowering stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The oil contains a total of 30.11% oxygenated sesquiterpenes, with caryophyllene oxide (15.14%) and α -muurolol (13.75%) being the dominant compounds in this class and cyperotundone (1.22%) being less abundant. Madani et al [ 30 ] compiled a table of the main components of the essential oils of D. viscosa from Algeria, Jordan, Italy, Turkey, Spain, and France. The composition of the oil of D. viscosa from Sardinia is most similar to the composition of the oil of Croatian D. viscosa in terms of caryophyllene oxide content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil contains a total of 30.11% oxygenated sesquiterpenes, with caryophyllene oxide (15.14%) and α -muurolol (13.75%) being the dominant compounds in this class and cyperotundone (1.22%) being less abundant. Madani et al [ 30 ] compiled a table of the main components of the essential oils of D. viscosa from Algeria, Jordan, Italy, Turkey, Spain, and France. The composition of the oil of D. viscosa from Sardinia is most similar to the composition of the oil of Croatian D. viscosa in terms of caryophyllene oxide content.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of the oil of D. viscosa from Sardinia is most similar to the composition of the oil of Croatian D. viscosa in terms of caryophyllene oxide content. Caryophyllene oxide is also the main component obtained by water distillation from the leaves of this species from Algeria and Tunisia [ 30 , 31 ]. The fatty acid and hydrocarbon groups represent less than 6% of the total oil ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Boudouda et al (2012) showed that the yield of I. viscosa essential oils ranged from 8 to 10% (obtained by solvant extractions). On the other hand, the yields of I. viscosa essential oils obtained from Sidi Rezine (Algeria) was 0.34% (Madani et al 2014). In the same region, Haoui et al (2015) found a yield ranging from 0.15 to 0.45%.…”
Section: Discussionmentioning
confidence: 97%
“…The essential oils chemical composition of I. viscosa growing in different countries have been investigated; in Island (Pistelli et al 2018), in Portugal (Miguel et al 2008); in Spain (Camacho et al 2000;Blanc et al 2006); in France (Blanc et al 2006); in Italy (De Laurentis et al 2002;Marongiu et al 2003); in Turkey (Blanc et al 2006;Sevindik et al 2017); in Jordan (Al-Qudah et al 2010); in Syria (Nasser et al 2014;Alalan et al 2015), in Lebanon (Assi et al 2010) in Tunisia (Sriti Eljazi et al 2018;Aissa et al 2019) and in Algeria (Madani et al 2014;Boudouda et al 2014;Haoui et al 2015) (Table 1). β-caryophyllene, tricosane, and isocostic acid characterized the populations of Algeria (Boudouda et al 2014;Madani et al 2014). The populations of Italy are characterized by 12-carboxy eudesma-3-11 (13)-diene (De Laurentis et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has been detected in volatile extracts of I. verbascifolia ssp. parnassica (Tzakou et al, 2001) , I. cappa (Priydarshi et al, 2016), I. crithmoides (Tsoukatou and Roussis, 1999), and I. viscosa (Madani et al, 2014). Methyl jasmonate, detected in remarkable concentration of 1.0% in the studied oil is a compound isolated from Jasmine flowers (Adams, 2009).…”
Section: Resultsmentioning
confidence: 99%